Analisis Risiko Keamanan Pada Aplikasi Mobile Banking Dan Strategi Mitigasi - Abdul Sakti; Ahmad Naswin; Sulkifli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to analyse security risks in mobile banking applications and their mitigation strategies. A qualitative approach using descriptive methods was employed, with data collected through literature reviews, documentation, and analysis of scientific literature relating to cybersecurity and mobile banking. The study focuses on identifying the types of risks, their sources, the resulting impacts, and the mitigation strategies implemented by banking institutions. The analysis was conducted systematically through the stages of data reduction, data presentation, and drawing conclusions, and was validated through triangulation of sources. The research findings indicate that the primary threats to mobile banking applications include phishing, malware, man-in-the-middle attacks, data breaches, and the use of weak passwords. Technical factors such as system and network vulnerabilities, as well as human factors—particularly user security awareness—are the main causes of these risks. Effective mitigation strategies include the implementation of multi-factor authentication, data encryption, real-time system monitoring, user education, and the development of applications based on secure coding. The combination of security technology, system monitoring, and user literacy has been proven to enhance mobile banking security, making the service safer, more reliable, and adaptable to evolving risks.